The Indonesian State Law System Is Based on The Philosophy of Pancasila and Constitution - Arsyad Aldyan (Res Judicata, 2023)
The State of Indonesia is a legal state which, of course, has a different legal system from other countries, where the difference in the legal system of the Indonesian state is this Indonesian state applies several existing legal systems, including applying some of the characteristics of the legal system of continental Europe, Anglo Saxon, and also the Islamic Law System. The primary basis in the formation of law in the state of Indonesia is Pancasila, besides that this Pancasila, which is also the ideology of the Indonesian state, is also used as a reference in the legal system in the State of Indonesia, with the existence of Pancasila all differences in customs, ethnicity, race, religion, and culture can be united to can accommodate all the legal interests of the Indonesian people, of course, the legal system used in this State of Indonesia is a legal system based on Pancasila as the state ideology. The legal system in Indonesia recognizes the existence of customary law and Islamic law because this Indonesian state has many customary law communities, and the majority of the population is Muslim, so that with this, the state legal system based on Pancasila, of course, also includes law. Customary law and Islamic law in the legal system in Indonesia. In the context of developing law in Indonesia, of course, also proclaiming the values of Pancasila, the implementation of the fourth principle of Pancasila, namely law-making is carried out through democracy led by wisdom in representative deliberation, and in the context of law enforcement in Indonesia, of course, must also prioritize values. Social justice. Keywords: Legal System, Pancasila, State of Law.